Prenatal Tobacco Exposure, Maternal Postnatal Nicotine Dependence and Adolescent Risk for Nicotine Dependence: Birth Cohort Study - De Genna, Natacha M. (Neurotoxicol Teratol, 2017)
AIMS: The goals of this study are to determine if there is (a) a threshold effect for prenatal tobacco exposure (PTE) on adolescent risk for nicotine dependence, and (b) an additive effect of PTE and maternal postnatal nicotine dependence on adolescent risk for nicotine dependence. METHODS: Pregnant women were recruited in their 4(th) or 5(th) gestational month and asked about cigarette use during the first trimester. Mothers reported on third trimester cigarette use at delivery. Sixteen years post-partum, mothers and offspring reported on current levels of cigarette use (N = 784). Nicotine dependence was assessed in both using a modified Fagerstrom questionnaire. RESULTS: Based on the results of a threshold analysis for PTE, four groups were created: threshold PTE only (10+ cigarettes per day), maternal nicotine postnatal dependence with no-low PTE (0–<10 cigarettes per day), threshold PTE + maternal postnatal nicotine dependence, and a referent group with no-low PTE and no maternal postnatal nicotine dependence. Adolescents in the PTE-only group and the PTE + maternal postnatal nicotine dependence group were significantly more likely to be at risk for nicotine dependence than the offspring from the referent group. However, there was no evidence for an additive effect of maternal postnatal nicotine dependence, and maternal nicotine dependence was not a significant predictor of adolescent risk for nicotine dependence in regression models including prenatal tobacco exposure. CONCLUSIONS: Bivariate analysis revealed a threshold effect for PTE of 10 cigarettes per day. In multivariate analysis, PTE remained significantly related to risk for offspring nicotine dependence, after controlling for maternal postnatal nicotine dependence and other covariates associated with adolescent cigarette use.